Influence of Processing Conditions on Microstructure and Mechanical Properties of Large Thin-Wall Centrifugal Ti–6Al–4V Casting. Issue 4 (April 2016) - Feng, Xin; Qiu, Jianke; Ma, Yingjie; Lei, Jiafeng; Cui, Yuyou; Wu, Xinhua; Yang, Rui
Abstract : In this work, the effects of mould pre-heating temperatures and hot isostatic pressing (HIPping) process on the microstructural characteristics and mechanical properties, including static tensile and damage-tolerance properties of large thin-wall cylindrical Ti–6Al–4V casting, have been studied. The experimental results show that with the increasing mould pre-heating temperature from 673 to 873 K, the casting microstructures change from a mixture of Widmanstätten and colony microstructure to a primary colony. The centre of the thick wall section has relatively coarse microstructure than the edge and thin section. Lower mould pre-heating temperature brings about more porosities. HIPping process, which not only reduces the casting pores effectively but also increases the prior β grain boundary cohesion and coarsens the microstructure, is essential to improving the ductility of the casting. Due to the oxygen contamination and finer microstructure on the surface, micro-hardness profiles on the cross section present a decreasing tendency from the surface to inner. The thickness of the reaction layers for the different mould pre-heating temperatures is nearly the same (~450 µm). On the whole, the tensile strength and micro-hardness decrease with increasing mould pre-heating temperature from 673 to 873 K. However, the fracture toughness and fatigue crack growth resistance of the castings increase with increasing mould pre-heating temperature.